Tools of Mathematical Modeling of the Implementation of Innovative Projects in the Enterprise - TATUEV, Arsen Azidovich; ZHANKAZIEVA, Zalina Nurmuhamedovna; ROKOTYANSKAYA, Violetta Valerievna; SAKHAROVA, Larisa Anatolievna; STENKINA, Elena Nikolaevna (Journal of Advanced Research in Law and Economics; Vol 6 No 2 (2015): JARLE Volume VI Issue 2(12) Summer 2015, 2016)
This paper presents the stochastic optimization methods in socio-economic systems. The authors proposed a stochastic model of optimal output. The practical guidelines on optimization in industrial systems are designed. In order to develop production plans the authors proposes a specific model of stochastic optimization. It is proposed to use the model not alone, but in conjunction with the method of analysis and evaluation of programs. This method allows designing complex manufacturing systems in conditions of uncertainty.
Keywords: methods of stochastic optimization, social and economic systems, mathematical model, linear programming